Avaliação das alterações comportamentais, eletrencefalográficas e da oxidação protéica induzidas pela injeção intraestriatal de ácido propiônico em ratos. - Rigo, Flávia Karine (2005)
Propionic acid (PA) is found in high amounts in tissues of patients with propionic acidemia, an inherited disorder of amino acid and lipid metabolism caused by severe deficiency of propionil-CoA-carboxylase activity. PA levels in blood and cerebral spinal fluid (CSF) usually reach 2,5- 5,0 mM during crises and can be much higher in the neuronal cells. Among the neurologic symptoms often presented, psychomotor delay/mental retardation, focal and generalized convulsions, cerebral atrophy and abnormalities are the most frequent. After cannula placing, rats received unilateral intrastriatal injections de PA (0,6; 2 and 6 μmol), MK-801 (3 nmol)+PA (6 μmol) or NaCl (9μmol). The effect of the intrastriatal administration of propionic acid on the behavior of rats in an open field and on EEG recording was assessed. PA caused convulsions and increased PA-induced protein carbonylation. MK-801 administration prevented PAinduced convulsions and protein carbonilation. These results suggest the involvement of NMDA receptors and oxidative stress in the PA-induced behavioral alterations.